Plumbagin Suppresses Breast Cancer Progression by Downregulating HIF-1α Expression via a PI3K/Akt/mTOR Independent Pathway under Hypoxic Condition - Supawan Jampasri; Somrudee Reabroi; Duangjai Tungmunnithum; Warisara Parichatikanond; Darawan Pinthong (Molecules, 2022)
Hypoxia-inducible factor-1α (HIF-1α) is a major transcriptional regulator that plays a crucial role in the hypoxic response of rapidly growing tumors. Overexpression of HIF-1α has been associated with breast cancer metastasis and poor clinical prognosis. Plumbagin, the main phytochemical from Plumbago indica, exerts anticancer effects via multiple mechanisms. However, its precise mechanisms on breast cancer cells under hypoxic conditions has never been investigated. This study aims to examine the anticancer effect of plumbagin on MCF-7 cell viability, transcriptional activity, and protein expression of HIF-1α under normoxia and hypoxia-mimicking conditions, as well as reveal the underlying signaling pathways. The results demonstrate that plumbagin decreased MCF-7 cell viability under normoxic conditions, and a greater extent of reduction was observed upon exposure to hypoxic conditions induced by cobalt chloride (CoCl2). Mechanistically, MCF-7 cells upregulated the expression of HIF-1α protein, mRNA, and the VEGF target gene under CoCl2-induced hypoxia, which were abolished by plumbagin treatment. In addition, inhibition of HIF-1α and its downstream targets did not affect the signaling transduction of the PI3K/Akt/mTOR pathway under hypoxic state. This study provides mechanistic insight into the anticancer activity of plumbagin in breast cancer cells under hypoxic conditions by abolishing HIF-1α at transcription and post-translational modifications.